Evaluation of 24-hour nutrition intake in indoor hockey student-athletes - Hambali, Sumbara; Rizal, Arman Khoirul; Alpen, Joni; Rizal, Rony M; Juditya, Silvy (Journal Sport Area, 2024)
Background Problems: Nutrition is an important factor in improving athlete performance, but many athletes still experience problems such as ignorance about the right portion and type of food, unbalanced energy intake, and a lack of knowledge about the nutrients the body needs. Research Objectives: This study aims to evaluate the nutritional intake of hockey student-athletes who are members of indoor hockey clubs in Tangerang City. Methods: This study used a quantitative descriptive method with a survey approach. Data were collected using a single and 24-hour reported food recall, and as many as 24 research subjects were involved in this study, there are student-athletes in the club’s indoor hockey in Tangerang City. Data analysis used a statistical approach in the form of percentages. The nutritional analysis in this study focused more on the percentages of carbohydrate, protein, fat, and caloric intake eaten by athletes within a 24-hour period. Findings and Results: This study showed the average results of the nutrition intakes include 83% for protein, 53% for carbohydrates, 72% for fat, and 52% for calories. The results show that the knowledge of indoor hockey athletes was still lacking. Conclusion: The findings of this study indicate that the nutritional intake of indoor hockey athletes in Tangerang City is still far from optimal. It is vital for athletes to enhance their understanding of proper nutrition and energy needs, as this can significantly impact their fitness levels and performance outcomes. Coaches and trainers should prioritise nutrition education as part of regular training programs, collaborating with nutritionists to ensure that athletes receive the necessary guidance on their dietary habits. In the future, developing integrated nutritional programs tailored to the specific needs of indoor hockey athletes will be crucial. This research contributes to a growing understanding of the importance of nutrition in sports and underscores the need for continued efforts to address the dietary challenges faced by student athletes.